Momentum Factor Effect on the Explanatory Power of Fama -French Three-Factor Model: Evidence from Tehran Stock Exchange (مجله دانش حسابداری, 2013)
Abstract We empirically tested, in Tehran Stock Exchange (TSE), the validity of the Carhart (1997) four-factor model by adding the price momentum factor as the fourth explanatory variable into the Fama-French three-factor model. The results imply that growth portfolio in comparison to value portfolio and also winner portfolio to loser portfolio have higher returns. However, with regard to Size factor no clear trend was observed. The average adjusted R2 across eight portfolios for single factor CAPM model, Fama-French three-factor model and Carhart four-factor model has been respectively 0.26, 0.50, and 0.56 showing a significant improvement in the four-factor model by adding the momentum factor to Fama-French model. Robustness of the Carhart four-factor model is also checked for two effects: up and down market conditions and seasonal behavior.